Security, Privacy, and Applied Cryptography Engineering 4th International Conference, SPACE 2014, Pune, India, October 18-22, 2014. Proceedings - Chakraborty, Rajat Subhra; Matyas, Vashek; Schaumont, Patrick (Security and Cryptology, 2014)
This book constitutes the refereed proceedings of the 4th International Conference on Security, Privacy, and Applied Cryptography Engineering held in Pune, India, in October 2014. The 19 papers presented together with two invited papers were carefully reviewed and selected from 66 submissions. The papers are organized in topical sections on cryptographic building blocks; mini tutorial; attacks and countermeasures; tools and methods; and secure systems and applications.